COMPARATIVE ANALYSIS OF CLINICAL-LABORATORY INDICATIONS IN PATIENTS WITH GIARDIASIS WITH CONVENTIONAL TREATMENT. - Khuzhakulov Davron Abdihakimovich (TADQIQOTLAR.UZ, 2024)
Annotation. Giardiasis is a disease caused by giardia excavators that parasitize the small intestine of humans and some animals. According to WHO, about 200 million people are infected with giardia every year (countries in Asia, Africa, Latin America). The  intensive  rate  per  100,000  population:  in  Russia  -  90.0  (among  the  total population) and 350.0 (among children under 14 years old); in the USA, Vermont - 42.3, New York State - 20.3 (1992-1997). Clinical manifestations of giardiasis are registered in almost 500 million patients per year worldwide.